Biological sulfate reduction rate measurements in cores from Peru continental margin of RV SONNE cruise SO147 - Kallmeyer, Jens (PANGAEA, 2025)
This dataset provides sulfate reduction rate data, measured with radiotracer incubations. Samples originate from the Peru continental margin, taken during SONNE Cruise SO147 in May-July 2000. Sediment samples from the uppermost ca. 20 cm were taken with a Multicorer (MUC), deeper samples down to ca. 4 m with a gravity corer (GC). Radiotracer incubations were carried out on board, incubation lasted 24 hrs at approximate in-situ temperature (4°-14°C). After termination of the incubations, the samples were sent back to MPI Bremen for quantification of SRR, using the single-step hot chromium distillation of Fossing & Jørgensen (1989, doi:10.1007/BF00002889)
Keywords: Peru continental margin; sulfate reduction rates; Upwelling